ANALYSIS OF FACTORS RELATED TO MIDWIFE CAREER DEVELOPMENT IN PUSKESMAS PLUS PERBAUNGAN, SERDANG BEDAGAI REGENCY - Sari, Yunita; Barita Aritonang; Rahmad Gurusinga (JURNAL KESMAS DAN GIZI (JKG), 2023)
Performance problems have become a serious problem for any agency at this time, and good performance certainly guarantees good service quality. Therefore, providing training and career development to employees is very important to carry out organizational goals effectively and efficiently. Based on preliminary research at the Perbaungan Plus Health Center, it showed that midwives' career development obstacles were: Inadequate administrative support, poor performance by midwives, and lack of guidance in career development. The purpose of this study was to determine the factors related to the career development of midwives at the Perbaungan Plus Health Center, Serdang Bedagai Regency. The research design used in this research is an analytical survey using a cross-sectional study. The research population consisted entirely of midwives and numbered 43 people using a total-sampling technique with 43 people. Data collection methods include primary data, secondary and tertiary. The data analysis used was univariate and bivariate analysis using the chi-square statistical test. The results showed that employee personality p(0.001), external factors p(0.001), compensation structure p(0.004), and organizational politics p(0.024) are related to the midwife's career development. The relationship between employees and organizations does not depend on the development of the midwifery profession p(0.431). The results of the study concluded that employee personality, external factors, and internal compensation systems and policies are related to midwifery professional development, while employee relations with organizations are related to midwifery professional development, meaning not. It is hoped that the Puskesmas can develop policies that focus on midwives in all aspects, including training in good organizational management and professional responsibility, improving employee welfare and creating a comfortable work environment.